Comparative power density and exergy density analyses of a regenerative supercritical carbon dioxide power cycle - Karakurt, Asim Sinan; Iskenderli, Semih; Ozel, Ibrahim Furkan (INDERSCIENCE ENTERPRISES LTD, 2023)
Many ways exist to balance the supply and demand of energy. However, this balance must be sustainable, environmentally friendly, and economical these days. Most existing technologies meet these requirements, but their use has only recently become widespread due to both political and technical reasons. This study investigates the effects of different design parameters on the first and second laws of thermodynamics based on the performance criteria of a regenerative supercritical carbon-dioxide (sCO(2)) cycle with intercooling and reheating. The results show the design parameters providing the optimum values to vary according to the maximum power density and mean cycle pressure values.
Keywords: mean cycle pressure; maximum power density; optimisation; supercritical carbon dioxide; ENGINE; IMPROVEMENT; EFFICIENCY; Thermodynamics; Energy & Fuels